Ефективне застосування комп'ютерної програми тестового контролю знань студентів - Пильов, Володимир Олександрович; Пильова, Тетяна Кузьмівна (НТУ "ХПІ", 2007)
The analysis of the communal methodical approaches of check of a level of knowledge is carried out through test programmes. Are proposed and the special functional capabilities of the exerciser on to the closed task are realised, which one are aimed at rise of a level of opening-up of the students. The procedure of designing of the tests of a given level of veracity of an evaluation of a level of knowledge on the four-ball system and ECTS system is advanced.
Keywords: Болонська декларація; кредитно-модульна система; формалізований контроль знань; педагогічний тест; комп'ютерне педагогічне тестування